2016
DOI: 10.1002/bit.26194
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cellulase recovery without β‐glucosidase supplementation for cellulosic ethanol production using an engineered strain and surfactant

Abstract: Recycling cellulases by substrate adsorption is a promising strategy for reducing the enzyme cost of cellulosic ethanol production. However, β-glucosidase has no carbohydrate-binding module (CBM). Thus, additional enzymes are required in each cycle to achieve a high ethanol yield. In this study, we report a new method of recycling cellulases without β-glucosidase supplementation using lignocellulosic substrate, an engineered strain expressing β-glucosidase and Tween 80. The cellulases and Tween 80 were added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…An important prerequisite for enzymatic hydrolysis is the effective adsorption of cellulases on the surface of lignocellulose, which can be either reversible or irreversible. After hydrolysis, some cellulases are released into the supernatant (liquid phase), while others stay attached to the residual substrate (solid phase). Although solution-phase cellulases can be readsorbed on fresh substrates for recycling or be collected by ultrafiltration, these methods cannot be used to directly recover substrate-bound enzymes. Therefore, the dynamics of cellulase adsorption on cellulose substrates under various conditions needs to be elucidated to be able to modulate lignocellulose hydrolysis and cellulase recovery. , …”
Section: Introductionmentioning
confidence: 99%
“…An important prerequisite for enzymatic hydrolysis is the effective adsorption of cellulases on the surface of lignocellulose, which can be either reversible or irreversible. After hydrolysis, some cellulases are released into the supernatant (liquid phase), while others stay attached to the residual substrate (solid phase). Although solution-phase cellulases can be readsorbed on fresh substrates for recycling or be collected by ultrafiltration, these methods cannot be used to directly recover substrate-bound enzymes. Therefore, the dynamics of cellulase adsorption on cellulose substrates under various conditions needs to be elucidated to be able to modulate lignocellulose hydrolysis and cellulase recovery. , …”
Section: Introductionmentioning
confidence: 99%
“…While β-glucosidase is negligibly recovered during the cellulase recycling process, we propose the combination of recycling cellulase with an engineered yeast strain expressing heterologous β-glucosidase to reduce the β-glucosidase supplementation and the cost of enzymatic hydrolysis for ethanol production . Furthermore, to avoid additional β-glucosidase supplementation, we have also reported a novel method of recycling cellulases with the engineered yeast strain and Tween 80, presenting excellent ethanol production over three cycles . These results demonstrated that we have developed a simple, practical, and low-cost enzyme recycling strategy to reduce the cost of enzymatic utilization for the production of cellulosic ethanol.…”
Section: Introductionmentioning
confidence: 78%
“…25 Furthermore, to avoid additional β-glucosidase supplementation, we have also reported a novel method of recycling cellulases with the engineered yeast strain and Tween 80, presenting excellent ethanol production over three cycles. 26 These results demonstrated that we have developed a simple, practical, and low-cost enzyme recycling strategy to reduce the cost of enzymatic utilization for the production of cellulosic ethanol. In this study, a recycling corncob pretreatment and cellulose hydrolysis were investigated for high-efficiency utilization of corncobs to produce β-farnesene and reduce the cost of the lignocellulose pretreatment.…”
Section: ■ Introductionmentioning
confidence: 82%
“…Initially, it was pointed out that the NIS aided cellulase to desorb from cellulose to make more free cellulase to participate in cellulosic hydrolysis. Disrupting the substrate structure as well as stabilizing and stimulating enzyme activity were further thought as the positive influences of NIS on enzymatic hydrolysis of cellulose. , Nevertheless, Eriksson et al found that NIS hardly played any role as a substrate disrupter, an enzyme stabilizer, and an effector and explained that NIS improved EHLC by reducing the unproductive adsorption of the enzyme onto lignin . This has become the mainstream viewpoint, but there have been still different theories on NIS improving EHLC. Rocha-Martín et al observed that PEG4000 could promote the enzymatic hydrolysis efficiency of microcrystalline cellulose more significantly than that of steam explosion-treated crop straw and pointed out that the improvement effect of NIS on glucose release during enzymatic hydrolysis of pretreated lignocellulose had hardly any relation with lignin .…”
Section: Introductionmentioning
confidence: 99%